Phase I clinical and pharmacokinetic evaluation of the vascular-disrupting agent OXi4503 in patients with advanced solid tumors. - Patterson, D; Zweifel, M; Middleton, MR; Price, P; Folkes, L; Stratford, MR; Ross, P; Halford, S; Peters, J; Balkissoon, J; Chaplin, D; Padhani, A; et al. (2012)
PURPOSE: Preclinical studies show that OXi4503 (combretastatin A1 diphosphate, CA1P) is more potent than other clinically evaluated vascular-disrupting agents. EXPERIMENTAL DESIGN: Escalating doses of OXi4503 were given intravenously over 10 minutes on days 1, 8, and 15 every 28 days to patients with advanced solid tumors. RESULTS: Doses were escalated in single-patient cohorts from 0.06 to 1.92 mg/m(2), then expanded cohorts to 15.4 mg/m(2) in 43 patients. Common adverse drug reactions were hypertension, tumor pain, anemia, lymphopenia, and easily controllable nausea/vomiting and fatigue. Five patients experienced different drug-related dose-limiting toxicities, atrial fibrillation, increased troponin, blurred vision, diplopia, and tumor lysis. Prophylactic amlodipine failed to prevent adverse events. Pharmacokinetics showed dose-dependent linear increases in peak plasma concentrations and area under the curve value of OXi4503. One partial response was seen in a heavily pretreated patient with ovarian cancer. Dynamic contrast-enhanced MRI confirmed a dose effect and showed significant antivascular effects in 10 of 13 patients treated at doses of 11 mg/m(2) or higher. CONCLUSIONS: The maximum tolerated dose was 8.5 mg/m(2) but escalation to 14 mg/m(2) was possible with only temporary reversible cerebrovascular toxicity by excluding hypertensive patients. As a tumor response was seen at 14 mg/m(2) and maximum tumor perfusion reductions were seen at doses of 11 mg/m(2) or higher, the recommended phase II dose is from 11 to 14 mg/m(2).